Thông báo ngắn: Hoạt tính bảo vệ gan của axit asiatic tách từ cây rau má [Centella asiatica (L.) Urban] - Quỳnh Như, Võ Thị; Thu Hà, Lê Thị; Phương Thảo, Trần Thị; Lộc, Trần Văn (Vietnam Journal of Chemistry, 2016)
The liver-protective effect of asiatic acid isolated from the aerial parts of Centella asiatica has been evaluated using the paracetamol model with silymarin as positive control. Asiatic acid showed a significant liver-protective activity on mices with high level of paracetamol.